Experimental investigation of current free double layers in helicon plasmas - Sahu, B. B.; Tarey, R. D.; Ganguli, A. (Physics of plasmas, 2014)
The paper presents investigations of current free double layer (CFDL) that forms in helicon plasmas. In contrast to the other work reporting on the same subject, in the present investigations the double layer (DL) forms in a mirror-like magnetic field topology. The RF compensated Langmuir probe measurements show multiple DLs, which are in connection with, the abrupt fall of densities along with potential drop of about 24 V and 18 V. The DLs strengths e